1995
DOI: 10.1149/1.2048499
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Polishing‐Related Surface Damage in (0001) Silicon Carbide Substrates

Abstract: The nature and extent of surface damage in 6H-SiC substrates prepared by mechanical polishing have been studied using backscattering of ultraviolet light and cross-sectional transmission electron microscopy. When the basal plane surface is prepared by lapping or polishing with large size diamond abrasives, the surface roughness is about one-fifth the particle size, while the subsurface damage extends to a depth of about half the abrasive size. Under optimum conditions of particle size, vertical load, and relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 1 publication
1
28
0
Order By: Relevance
“…Therefore, SiC epitaxy is a key technology for producing device quality layers. Commercially available SiC wafers used for epitaxial growth still have a high density of polishing scratches on the substrate surface [1,2]. High density of structural defects, like micropipes, dislocation clusters and voids, in the substrate produce surface imperfections during polishing and enhance the surface roughness [3].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, SiC epitaxy is a key technology for producing device quality layers. Commercially available SiC wafers used for epitaxial growth still have a high density of polishing scratches on the substrate surface [1,2]. High density of structural defects, like micropipes, dislocation clusters and voids, in the substrate produce surface imperfections during polishing and enhance the surface roughness [3].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17] There are also reports on the quality of epi-films investigated from the view-point of surface preparation before starting the epi-film growth. 18,19) However, most of those works are based on the assumption that damage is introduced uniformly on the wafer surface, but not locally.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been reported to investigate the planarization of SiC [6,[10][11][12]. Based on the theory of crystallography and the research development of the hexagonal super-hard materials, such as gallium nitride (GaN), sapphire, 4H-and 6H-SiC [13][14][15][16][17][18], we know that all these materials have an obvious characteristics: if the (0 0 0 1) surface of wafer is approximately 0 • -off, the surface could emerge with atomic step-terrace structure after planarization [3,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%